Educoding: Media Pembelajaran Berbasis Website untuk Meningkatkan Kemandirian Belajar Siswa SMA - Salwa, Kemala Adinda; Bachri, Bachtiar Sjaiful; Kristanto, Andi (Akademika : Jurnal Teknologi Pendidikan, 2024)
This study aims to measure the feasibility and effectiveness of EduCoding in improving students' learning independence in informatics subjects in high school. This study uses a Research and Development (R&D) model based on the Borg & Gall model which includes 10 stages. The study was conducted at SMA Negeri 3 Nganjuk with a sample of 36 students from Class X for each as an experimental and control class. The data collection instrument was a questionnaire for validation by media experts, material experts, and learning design experts to measure students' learning independence. The results showed that EduCoding was validated as